2021
DOI: 10.25301/jpda.301.50
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Distal Carious Lesions in Mandibular Second Molars Due to Mesio-Angular Impacted Third Molars

Abstract: OBJECTIVE: This study was conducted to observe the relationship of mesio-angular impacted third molars to the development of distal caries in adjacent second molars. METHODOLOGY: This cross-sectional study was conducted at Nishtar Institute of Dentistry, Multan. Nine hundred and eighty nine periapical, bitewing and Panoramic radiographs were recorded and examined for distally carious second molars and impacted mandibular third molars. SPSS version 23.0 was used for data entry and analysis. RESULTS: Almost 40.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…7 Premature extraction of 3 rd molar is considered as a treatment option to prevent before time loss of 2 nd molar. 18 This concept is also supported by numerous studies. In order to come up with accurate treatment, studies with prolong observation period and follow ups are required.…”
Section: Discussionmentioning
confidence: 65%
“…7 Premature extraction of 3 rd molar is considered as a treatment option to prevent before time loss of 2 nd molar. 18 This concept is also supported by numerous studies. In order to come up with accurate treatment, studies with prolong observation period and follow ups are required.…”
Section: Discussionmentioning
confidence: 65%
“…While in a similar Pakistani study conducted by Ashar et al reported that most of the participants were of 23 to 29 years (39.7%), followed by 17 to 22 years (33.08%). 15 Another Pakistani study by Rauf et al also reported the highest frequency of 3 rd molar impaction in the 2 nd and 3 rd decades of life and every few people were of age greater than 40 years 16 . This might be because of the increasing knowledge about early extraction of impacted 3 rd molars and oral health 16 .…”
Section: Discussionmentioning
confidence: 95%
“…In the current study, the commonest type of impaction was mesio-angular impaction which is similar to previous studies conducted among different ethnicity and populations 22,23 . Previous Pakistani studies also revealed that mesio-angular impaction was the most common type of impaction 15,24 . The prevalence of dental caries in the second molar adjacent to 3 rd molars has been estimated to be as less as 1% to 5% to as high as 15% to 51% in previous studies [5][6][7]15 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations